(3QSGdI aj eSFdI Ndb GdbQBfs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje cdGeg GdYXje GfYGeg hHYO agPg QSGdI eYehdI ajeG jJYdb HeSFdI Ndb GdbQGf ef GdcdGe hGdaQbGf Hjf GdMb hGdHGWd s
(3BNQgG (B:s
(3ENJdahG ai hUa cdGe Gddg JYGdi ai GdGRd Hchfg GeQ fgjkG eNGWHJg dceG aCKHJ Pdc GdTjN GHh GdMSf GdGTYQi hfaGg YHOGddg Hf SYjO hWGFag cKjQg ai GdeJbOejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds